Irrigation Water Management in a Mediterranean Greenhouse District: Irrigation Adequacy Assessment1. (28th April 2015) - Sánchez, José A.; Reca, Juan; Martínez, Juan
Abstract The sustainability of greenhouse production in semi‐arid regions in the Mediterranean basin depends on the availability of water resources. However, the increasing demand for water has caused environmental and water availability concerns. The main objective of this work is to assess irrigation adequacy in an irrigation district located in southern Spain with major water resource problems in terms of both quantity and quality. Two resolution levels were considered: crop and farm. Relative irrigation supply (RIS) index was calculated for a wide sample of crops and farms in the area over the course of four consecutive agricultural seasons. An overall RIS value of 1.12 was obtained. This value indicates that irrigation water exceeded net irrigation needs and, consequently, moderate leaching fractions were applied. However, a high RIS variability was observed. The effect of several factors was statistically analysed to explain this variability. The average water supply to farms was slightly higher than that applied in similar greenhouse districts, possibly due to higher irrigation water salinity. The high variability in the annual relative water supply (ARIS) to the farms confirmed that the main source of variability was farmer management decisions. Irrigation performance in this area could be improved with a proper extension of good irrigation practices. Copyright © 2015 John Wiley & Sons, Ltd.